Insights Gained from Special Education Pre-Service Teachers Interviewing Paraprofessionals - Schulze, Rob (Journal of the American Academy of Special Education Professionals, 2020)
In this study 25 student teachers receiving endorsement in special education interviewed paraprofessionals and self-rated their ability to perform a variety of paraprofessional supervision tasks. The paraprofessionals expressed desires for increased training and skills in behavior management; increased training in general; communication with special educators; and respect as professionals. The student teachers stated that the interview process helped them set career goals and were helpful in preparing them to supervise paraprofessionals. They rated their ability to supervise paraprofessionals higher after the interviews. The results have implications for teacher preparation programs as the results note that there needs to be coursework that explicitly teaches supervision and management of paraprofessionals and which teaches preservice special educators to be trainers of paraprofessionals, not just teachers of students.